Sustainable Economy and Green Growth: Strategies for Promoting Environmentally Friendly Economic Development - Pudjowati, Juliani; Sesario, Revi; Muthmainnah, Riyadatul (PT. Anagata Sembagi Education, 2026)
Sustainable economy and green growth have become essential approaches to addressing the global challenge of balancing economic development with environmental sustainability and social welfare. This study aims to analyze how green growth strategies contribute to sustainable economic development through the integration of environmental, economic, and social dimensions. A qualitative research design with a descriptive-exploratory approach was employed. Data were collected through in-depth interviews, document analysis, and focus group discussions involving policymakers, experts, and stakeholders. The data were analyzed using thematic and content analysis to identify key patterns and relationships among variables. The results indicate that renewable energy development, green innovation, policy instruments, institutional governance, and sustainable natural resource management significantly contribute to environmentally friendly economic growth. These factors support the decoupling of economic growth from environmental degradation while promoting efficiency and long-term stability. The findings also highlight the importance of inclusive policies, such as green job creation and social protection, in ensuring equitable benefits of green growth. In conclusion, green growth is a comprehensive strategy that enables sustainable economic development by aligning economic progress with environmental protection and social inclusion. Effective implementation requires integrated policies, strong institutions, and continuous innovation.